Predictive value of peri-chemotherapy hematological parameters for febrile neutropenia in patients with cancer - Jia, Hongyuan; Liang, Long; Chen, Xue; Zha, Wenzhong; Diao, Wei; Zhang, Wei (Frontiers in Oncology, 2024)
Objective The study aimed to compare hematological parameters pre- and early post-chemotherapy, and evaluate their values for predicting febrile neutropenia (FN). Methods Patients diagnosed with malignant solid tumors receiving chemotherapy were included. Blood cell counts peri-chemotherapy and clinical information were retrieved from hospital information system. We used Lasso method for variable selection and fitted selected variables to a logistic model. We assessed the performance of the prediction model by the area under the ROC curve. Results The study population consisted of 4130 patients with common solid tumors receiving triple weeks chemotherapy regime in Sichuan Cancer Hospital from Feb 2019 to March 2022. In the FN group, change percentage of neutrophil count decreased less (-0.02, CI: -0.88 - 3.48 vs - 0.04, CI: -0.83 - 2.24). Among hematological parameters, lower post-chemotherapy lymphocyte count (OR 0.942, CI: 0.934 - 0.949), change percentage of platelet (OR 0.965, CI: 0.955 - 0.975) and higher change percentage of post-chemotherapy neutrophil count (OR 1.015, CI: 1.011 - 1.018), pre-chemotherapy NLR (OR 1.002, CI: 1.002 - 1.002) predicted an increased risk of FN. These factors improved the predicting model based on clinical factors alone. The AUC of combination model was 0.8275. Conclusions Peri-chemotherapy hematological markers improve the prediction of FN.